Socialization of trials smelter machine for making paving blocks from waste in plastic Dawuan village, Tengah Tani district - Johan Johan; Bastoni Bastoni; Martinus Agust Isa; Maulani Aniya; Wicaksono Freddy; Gunawan Harry; Nurudin Arif (BIO Web of Conferences)
Plastic waste management remains a critical challenge in global environmental preservation. In response to this issue, an innovative smelter machine was developed to convert plastic waste into eco-friendly paving blocks. This community service program was implemented in Dawuan Village, Tengah Tani District, with the aim of empowering local residents through hands-on training and the application of appropriate technology. The program followed three key stages: preparation, implementation, and monitoring and evaluation. A total of twenty participants engaged in the training and evaluation process. The results demonstrated a significant improvement in participants’ knowledge and skills, with moderate learning gains observed across the group. The intervention was found to be particularly effective for participants with limited prior knowledge. Moreover, the program was conducted with high levels of community engagement and enthusiasm. Beyond enhancing environmental awareness, the initiative created tangible economic opportunities by enabling local production of durable paving blocks. This appropriate technology not only supports plastic waste reduction but also contributes to improving the quality of life within the community. The success of this program highlights the potential of localized technological solutions in addressing environmental challenges and fostering sustainable community development.